Time Course of Cortical Activations in Implicit and Explicit Recall - Badgaiyan, Rajendra D. (J Neurosci, 1997)
The distinction between implicit and explicit retrieval of learned material is central to recent thinking about the neural systems underlying memory. Word stem completion is one task in which subjects can be instructed either to make a deliberate recall (explicit instruction) or to be told to complete the stem with any appropriate word (implicit instruction). Positron emission tomography (PET) studies have indicated that during implicit retrieval, there is reduced blood flow in right posterior areas, whereas some tasks of explicit retrieval involve frontal and hippocampal activation. However, there is no information about the timing of these activations or how implicit and explicit retrieval might be related. We used word stem completion tasks similar to those used in the PET studies, but used high-density electrical recording designed to allow localization of the regions involved in the tasks and to provide temporal information. We found reduced activity for primed words in right posterior cortex corresponding to previous PET results. The reduction occurred within the first 200 msec after input, suggesting early interaction with the information stored in this area. Similar reductions observed during explicit recall of the previously presented words indicate that priming is similar under implicit and explicit conditions. In addition, when priming was not an adequate basis for response, then frontal areas were active. Retrieval of unprimed words under implicit instruction elicited right frontal activation, whereas explicit retrieval activated frontal areas bilaterally. Left frontal and hippocampal activations appear to occur only when the retrieval involved use of the words from the list studied previously.